2015
DOI: 10.1016/j.spa.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

MRL order, log-concavity and an application to peacocks

Abstract: Highlights• We recall some properties of R + -valued homogeneous Markov processes which admit a totally positive transition kernel.• We establish the equivalence between the MRL ordering and a log-concavity type condition.• We exhibit new classes of MRL processes, i.e. integrable processes which increase in the MRL order. AbstractWe provide an equivalent log-concavity condition to the mean residual life (MRL) ordering for realvalued processes. This result, combined with classical properties of total positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In this paper, we provide a log-concavity characterization of the WDS ordering. This characterization is the same as that obtained in Bogso [4,Theorem 3.3] for the MRL ordering.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this paper, we provide a log-concavity characterization of the WDS ordering. This characterization is the same as that obtained in Bogso [4,Theorem 3.3] for the MRL ordering.…”
Section: Introductionsupporting
confidence: 80%
“…Here is a characterization of WDS ordering in terms of log-concavity for probability measures with negative mean. This characterization is the same as that of the MRL ordering obtained in Bogso [4,Theorem 3.3].…”
Section: )supporting
confidence: 74%
“…There are many results in the literature related to the construction of self-similar processes. In Madan-Yor [23], Fan-Hamza-Klebaner [10], Hamza-Klebaner [13], Hirsch-Profeta-Roynette-Yor [15], Bogso [6] and Henry-Labordère-Tan-Touzi [14], the authors provided many constructions of self-similar martingales with given marginal distributions. In particular, Madan and Yor [23], Hamza and Klebaner [13], and Henry-Labordère, Tan and Touzi [14] exhibited several examples of discontinuous fake Brownian motions.…”
Section: Introductionmentioning
confidence: 99%
“…Kellerer (1972) then showed that for ℝ-valued processes the martingale can in fact be chosen to be a Markov process. Recent contributions to the peacock literature include, next to the extensive work of Hirsch et al (2011), the articles by Bogso (2015Bogso ( , 2016, as well as Ewald and Yor (2015) who discuss applications in the economics of inequality. Further recent applications of peacocks involve Skorohod embeddings (see Källblad, Tan, & Touzi, 2017) and optimal transport under marginal constraints (see Beiglböck & Juillet, 2016).…”
Section: Introductionmentioning
confidence: 99%